A flexible multivariable model for Phytoplankton growth - Mohammad A. Tabatabai; Wayne M. Eby; Sejong Bae; Karan P. Singh (Mathematical Biosciences and Engineering)
We introduce a new multivariable model to be used to studythe growth dynamics of phytoplankton as a function of both time and theconcentration of nutrients. This model is applied to a set of experimentaldata which describes the rate of growth as a function of these two variables.The form of the model allows easy extension to additional variables. Thus, themodel can be used to analyze experimental data regarding the effects ofvarious factors on phytoplankton growth rate. Such a model will also be usefulin analysis of the role of concentration of various nutrients or traceelements, temperature, and light intensity, or other important explanatoryvariables, or combinations of such variables, in analyzing phytoplanktongrowth dynamics.